PALANTIR: An updated prediction tool for exoplanetary radio emissions - Mauduit, E.; Grießmeier, J.-M.; Zarka, P.; Turner, J. D. (My University, 2023)
In the past two decades, it has been convincingly argued that magnetospheric radio emissions, of cyclotron maser origin, can occur for exoplanetary systems, similarly as solar planets, with the same periodicity as the planetary orbit. These emissions are primarily expected at low frequencies (usually below 100 MHz, c.f. Farrell et al., 1999; Zarka, 2007). The radio detection of exoplanets will considerably expand the field of comparative magnetospheric physics and star-planet plasma interactions (Hess & Zarka, 2011). We have developped a prediction code for exoplanetary radio emissions, PALANTIR: "Prediction Algorithm for star-pLANeT Interactions in Radio". This code has been developed for the construction of an up-to-date and evolutive target catalog, based on observed exoplanet physical parameters, radio emission theory, and magnetospheric physics embedded in scaling laws. It is based on, and extends, previous work by Grie meier et al. (2007b). Using PALANTIR, we prepared an updated list of targets of interest for radio emissions. Additionally, we compare our results with previous studies conducted with similar models (Griessmeier, 2017). For the next steps, we aim at improving this code by adding new models and updating those already used.
Planetary, Solar and Heliospheric Radio Emissions IX
PUBLISHED